1998
DOI: 10.1002/(sici)1097-4652(199807)176:1<216::aid-jcp23>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary cell cultures from murine kidney and heart differ in endosomal pH

Abstract: Endosomal and lysosomal pH values have been determined for many established cultured cell lines of different origins. These cell lines may be grouped into two classes based on observed differences in pH of early (recycling) endosomes. Members of the first class typically have an early endosomal pH of 6.2, whereas members of the second class typically have an early endosomal pH of 5.4. Because established cell lines may have developed artificial differences in endosomal pH due to extended culture, it remains to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…In the first, we followed the uptake of fluorescent dextran conjugates as probe of fluidphase endocytosis at 37°C. When CM were incubated with FITC-Dx for a short time point (5 min) typically required for materials to reach the early endosomal compartments (Rybak and Murphy, 1998), we noted a punctuate fluorescence pattern: small vesicles containing FITC-dextran scattered throughout the cell's cytoplasm, mostly accumulated in the periphery of the CM presumably corresponding to early endosomes ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first, we followed the uptake of fluorescent dextran conjugates as probe of fluidphase endocytosis at 37°C. When CM were incubated with FITC-Dx for a short time point (5 min) typically required for materials to reach the early endosomal compartments (Rybak and Murphy, 1998), we noted a punctuate fluorescence pattern: small vesicles containing FITC-dextran scattered throughout the cell's cytoplasm, mostly accumulated in the periphery of the CM presumably corresponding to early endosomes ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that an increased expression of Rab1 GTPase in myocardium distorts sub-cellular localization of proteins and is sufficient to cause cardiac hypertrophy and failure (Wu et al, 2001). An enhanced acidification was observed in heart cell endosomes (pH 5.5) compared with kidney cell endosomes (pH 6.0) (Rybak and Murphy, 1998) suggesting that differences in endosomal pH may be important for the proper functioning of different cell types. Using rat cardiac myocytes it was demonstrated that the endocytic traffic is blocked in multivesicular carrier endosomes at and below 26°C, and that reduced temperature slows down transport in the recycling pathway, without a complete block (Punnonen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An MCP-based delivery system can exploit the lowered pH in maturing endosomes, which reaches pH 5, to disassemble and release its cargo. [30][31][32] Coupled with encapsulated cytolysin proteins, the now-released therapeutic cargo could escape the endosome and release into the cytoplasm of target cells. It is interesting that TEM images of partially disrupted MCPs, either by high temperature or extreme pH, show that MCP bodies persist, though they are misshapen and/or smaller in size than untreated MCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the new cell lines that support the effective replication of the human influenza viruses and have low endosomal pH are promising candidates for influenza vaccine production. Cultured mouse heart cells could be considered as an example, since they have more acidic endosomes (pH 5.5) than cultured mouse kidney cells (pH 6.0) [69].…”
Section: Resultsmentioning
confidence: 99%